Bolivia's radical tradition permanent revolution in the Andes - John, S. Sándor 1955- (University of Arizona Press, 2009)
In December 2005, following a series of convulsive upheavals that saw the overthrow of two presidents in three years, Bolivian peasant leader Evo Morales became the first Indian president in South American history. Consequently, according to S. Sándor John, Bolivia symbolizes new shifts in Latin America, pushed by radical social movements of the poor, the dispossessed, and indigenous people once crossed off the maps of "official" history. But, as John explains, Bolivian radicalism has a distinctive genealogy that does not fit into ready-made patterns of the Latin American left. According to its author, this book grew out of a desire to answer nagging questions about this unusual place. Why was Bolivia home to the most persistent and heroically combative labor movement in the Western Hemisphere? Why did this movement take root so deeply and so stubbornly? What does the distinctive radical tradition of Trotskyism in Bolivia tell us about the past fifty years there, and what about the explosive developments of more recent years? To answer these questions, John clearly and carefully pieces together a fragmented past to show a part of Latin American radical history that has been overlooked for far too long. Based on years of research in archives and extensive interviews with labor, peasant, and student activists—as well as Chaco War veterans and prominent political figures—the book brings together political, social, and cultural history, linking the origins of Bolivian radicalism to events unfolding today in the country that calls itself "the heart of South America."